Regulatory and Legal Construction of Mudharabah Financing in Islamic Banking: A Normative Review of the At-Tawazun Principle - Nugroho, Any; Suriani, Rollys (JURNAL AKTA, 2025)
This research examines the legal construction of mudharabah financing in the Indonesian Islamic banking system with a focus on the implementation of the at-tawazun (balance) principle. The research employs a normative legal research method using statutory and conceptual approaches. Primary legal materials include Law Number 21 of 2008 concerning Sharia Banking, regulations issued by the Financial Services Authority, and fatwas of the National Sharia Council of the Indonesian Ulema Council, while secondary materials consist of scholarly works on Islamic law and Islamic banking. The research findings indicate that the legal construction of mudharabah in Indonesia has accommodated the at-tawazun principle through proportional risk and profit sharing between Islamic banks as shahibul maal and customers as mudharib. However, its implementation still faces challenges regarding information asymmetry, moral hazard, and suboptimal legal protection. The at-tawazun principle is reflected in the profit and loss sharing mechanism that requires both parties to share risks fairly according to their respective contributions. This research concludes that regulatory improvements are needed to strengthen the implementation of the at-tawazun principle in mudharabah financing, particularly in aspects of transparency, accountability, and more effective dispute resolution mechanisms to achieve justice and balance in Islamic banking contractual relationships.